Integrating Blockchain Technology with Internet of Things and Edge Computing to Achieve Security - Gupta, Tejasvee; Patel, Hiren B (Journal of Ecohumanism, 2024)
The last decade has seen many advancements and emergence in computing technologies; Internet of Things (IoT) being one of the most successful among them. Huge data generation in IoT can be utilized for analysis and monitoring the behaviour of various patterns. In spite of wide adaptability, IoT has various challenges such as privacy, security and computational constraints. To address the later challenge, Edge computing can be a potential solution with great computational resources leading towards the improvement in performance in terms of latency, throughput and response time. However, privacy and security remain largely unaddressed along with the traditional limitations of a centralized approach. This brings into the usage of another technology viz. Blockchain that handles the issue of privacy and security through its inherent features such as immutability, transparency and decentralization. In this research, we intend to explore the option of possible integration of Blockchain technology with IoT to address these challenges.